Social Organization and Economic Development - Николь Биггарт (Journal of Economic Sociology, 2010)
In this paper I try to disprove the neoclassical assumption that all the markets should be similar to each other and their distinctions testify to their imperfection. Instead of speaking about the market model, taken in the economic theory I suggest the alternative view on the markets and market operation based on the four main assumptions. I claim that this point of view has been proved by the results of observations, and the social policy based on it turned out to be more reliable.